Revisiting the Role of Aspirin for the Primary Prevention of Cardiovascular Disease. Issue 13 (24th September 2019) - Marquis-Gravel, Guillaume; Roe, Matthew T.; Harrington, Robert A.; Muñoz, Daniel; Hernandez, Adrian F.; Jones, W. Schuyler
Abstract : Aspirin is the cornerstone of the antithrombotic management of patients with established atherosclerotic cardiovascular disease, but major guidelines provide conflicting recommendations for its use in primary prevention. Findings from recent randomized trials totaling >47 000 patients called into question the net clinical benefits of aspirin in primary prevention for 3 key populations: patients with diabetes mellitus, community-dwelling elderly individuals, and patients without diabetes mellitus who are at intermediate risk for atherosclerotic events. In the context of increasing emphasis on the use of other treatments for primary prevention in patients with moderate-high future risk of developing atherosclerotic cardiovascular disease, the efficacy and safety of aspirin for primary prevention has become uncertain. Key unresolved questions regarding the role of aspirin in primary prevention include the optimal drug formulation, dosing schedule, weight-based dose selection, and interplay between sex and treatment response. In the current era, most patients without established atherosclerotic cardiovascular disease should not be prescribed aspirin. Rather, aggressive management of comorbidities tailored to the expected cardiovascular risk needs to be emphasized. In this context, informed shared decision making between clinicians and patients regarding the use of aspirin for primary prevention of cardiovascular events is a suitable and laudable approach. In this article, we revisit the role of aspirin for the primary prevention of cardiovascular diseases by critically reviewing the key scientific literature, highlight key areas of uncertainties for future research, and propose a decisional framework for clinicians to support prescription of aspirin in primary prevention.